P025 Comparison of abdominal lymph nodes between healthy volunteers and patients with Crohn's disease. (25th January 2019) - Williams, H; Hoad, C; Scott, R; Aithal, G; Marciani, L; Moran, G; Gowland, P
Abstract: Background: Crohn's disease (CD) causes changes in the lymphatic system which have been studied using MRI. Dfusion Weighted Imaging with Background Suppression (DWIBS) provides a powerful method to isolate the nodes which are otherwise hard to identify on 3T images. DWIBS has been used to show a difference in Apparent Diffusion Coefficient (ADC) between benign and malignant enlarged nodes but work in inflammatory diseases is absent, and T2 measures may provide additional information on inflammatory activity. We hypothesised that lymph node ADC, T2, size and number may be useful disease activity measures. Aim: to undertake a pilot study to investigate ADC, T2, number and size of abdominal lymph nodes in healthy volunteers and CD patients. Methods: Healthy participants (HP) and CD patients were scanned on a Phillips 3T Ingenia (Best, the Netherlands). CD patients had active disease (CRP of >5 mg/dl or faecal calprotectin (FCP) of >250 μg/g or ileocolonoscopy or MR enterography). Slices were orientated sagittally, respiratory triggering was used to reduce through plane motion. The DWIBS sequence was used to measure ADC and T2. The length of the major and minor axes of the lymph nodes were recorded. Results: HP (4 males, 3 females, mean age 32 ± 13 years) and patients with CD (3 males, 3 females, mean age 29 ± 11 years) were recruited. In CD, CRP was 7.9 ± 2.9 mg/dl and FCP was 755 ± 225 μg/g. Figure 1 shows lymph nodes identified on DWIBS images. Top: Healthy volunteer. Bottom: CD patient. Two lymph nodes shown for each by the red arrows on an ADC image on the left and the same two nodes on a T2 image on the right. ADC, T2 and length of the major and minor axis calculated for each group as a whole along with the standard error of the mean. The p values for comparisons between the healthy volunteers and CD patients with significant changes highlighted. Violin plot showing the distribution of the measurements from the healthy volunteers and CD patients. Fewer nodes were identified in CD than in the HP, but this was highly dependent on the quality of respiratory triggering which was worse in CD patients. Conclusions: The size of the lymph nodes increased and ADC decreased in CD probably, indicating an increase in cellularity of inflamed lymph nodes. A non-significant increase in T2 was noted in CD possibly reflecting the inflammatory response in the lymph node. Lymph node size, ADC and T2 could provide a novel inflammatory marker in CD. These data need replicating in larger cohorts with changes after CD therapy assessed.